Cost-utility analysis comparing laparoscopic vs open aortobifemoral bypass surgery - Krog, Anne Helene (Vasc Health Risk Manag, 2017)
OBJECTIVES: Laparoscopic aortobifemoral bypass has become an established treatment option for symptomatic aortoiliac obstructive disease at dedicated centers. Minimally invasive surgical techniques like laparoscopic surgery have often been shown to reduce expenses and increase patients’ health-related quality of life. The main objective of our study was to measure quality-adjusted life years (QALYs) and costs after totally laparoscopic and open aortobifemoral bypass. PATIENTS AND METHODS: This was a within trial analysis in a larger ongoing randomized controlled prospective multicenter trial, Norwegian Laparoscopic Aortic Surgery Trial. Fifty consecutive patients suffering from symptomatic aortoiliac occlusive disease suitable for aortobifemoral bypass surgery were randomized to either totally laparoscopic (n=25) or open surgical procedure (n=25). One patient dropped out of the study before surgery. We measured health-related quality of life using the EuroQol (EQ-5D-5L) questionnaire at 4 different time points, before surgery and for 6 months during follow-up. We calculated the QALYs gained by using the area under the curve for both groups. Costs were calculated based on prices for surgical equipment, vascular prosthesis and hospital stay. RESULTS: We found a significantly higher increase in QALYs after laparoscopic vs open aortobifemoral bypass surgery, with a difference of 0.07 QALYs, (p=0.001) in favor of laparoscopic aortobifemoral bypass. The total cost of surgery, equipment and hospital stay after laparoscopic surgery (9,953 €) was less than open surgery (17,260 €), (p=0.001). CONCLUSION: Laparoscopic aortobifemoral bypass seems to be cost-effective compared with open surgery, due to an increase in QALYs and lower procedure-related costs.